Synthesis of a novel biphenyl epoxy resin and its hybrid composite with high thermal conductivity. Issue 7 (4th September 2018) - Na, T.; Che, S.; Sun, Y.; Liu, X.; Hao, J.; Zhao, C.
ABSTRACT: A novel biphenyl epoxy monomer of p ‐methyl phenylhydroquinone epoxy resin ( p ‐MEP) was synthesized and characterized. We researched its potential in the area of thermal conduction application and prepared a series of hybrid composites based on it with different mass ratios of sphere Al2 O3 filler. From the good mobility and low viscosity of p ‐MEP, it allowed mixing with more Al2 O3 fillers. The hybrid epoxy resins owned the advantages of traditional epoxy resins as well as quite considerable thermal conductivity. Therefore, the hybrid composite at the maximum mass fraction of 70% possess the highest thermal conductivity of 5.6 W mK −1, which is 5.6 times higher than that of pristine p ‐MEP (0.1 W mK −1 ). © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47078. Abstract : A novel biphenyl epoxy resin and its hybrid composites with different mass ratios of sphere Al2O3 filler were prepared. They showed high thermal conductivity.